2007
DOI: 10.1128/iai.00334-07
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Helicobacter pylori Virulence Factors and Associated Expression Profiles of Inflammatory Genes in the Human Gastric Mucosa

Abstract: Helicobacter pylori virulence factors have been suggested to be important in determining the outcome of infection. The H. pylori adhesion protein BabA2 is thought to play a crucial role in bacterial colonization and in induction of severe gastric inflammation, particularly in combination with expression of CagA and VacA. However, the influence of these virulence factors on the pathogenesis of H. pylori infection is still poorly understood. To address this question, the inflammatory gene expression profiles for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 55 publications
1
13
1
Order By: Relevance
“…Concerning cytokine levels, no association between corpus and antrum mucosal concentrations of IL-1␤ and TNF-␣ with respect to CagA/ VacA status was observed. These findings are consistent with a number of previous studies that reported similar gene expression patterns in the gastric mucosa of patients infected with different H. pylori strains, suggesting that the expression levels of some cytokines, including IL-1␤ and TNF-␣, are independent of the presence of cagA or vacA genes [44,55,56]. On the other hand, the prevalence of infection with H. pylori or cagA/vacA strains resulted in no differences among carriers of the IL1 and TNF gene polymorphisms analyzed in this study.…”
Section: Discussionsupporting
confidence: 94%
“…Concerning cytokine levels, no association between corpus and antrum mucosal concentrations of IL-1␤ and TNF-␣ with respect to CagA/ VacA status was observed. These findings are consistent with a number of previous studies that reported similar gene expression patterns in the gastric mucosa of patients infected with different H. pylori strains, suggesting that the expression levels of some cytokines, including IL-1␤ and TNF-␣, are independent of the presence of cagA or vacA genes [44,55,56]. On the other hand, the prevalence of infection with H. pylori or cagA/vacA strains resulted in no differences among carriers of the IL1 and TNF gene polymorphisms analyzed in this study.…”
Section: Discussionsupporting
confidence: 94%
“…and babA2?) and duodenal ulcers have been found in Portugal, Germany, Finland and Cuba, however, no such association have been observed in Sweden (Olfat et al 2005;Wen et al 2007;Torres et al 2009). Similarly, in the present study, no differences in the prevalence of gene combinations were observed between the ulcer and non-ulcer patients for the ''triple-positive'' (vacA s1-cagA-babA2?)…”
Section: Discussioncontrasting
confidence: 78%
“…strains [20]. Although results from many studies have shown CagA to be associated with a more severe inflammatory response and more severe pathological changes [17,18], results from some investigations have also demonstrated that expression of cytokines, including IL-6, IL-8, IL-10 and TNF-a, was not influenced by H. pylori virulence factors such as CagA [21][22][23][24]. Moreover, the polymorphisms in genes encoding some cytokines, for example IL-1, TNF-a and IFN-c, have been associated with H. pylori-induced gastric adenocarcinoma and peptic ulcers [25].…”
Section: Discussionmentioning
confidence: 90%